CONSTRUCTIVIST THEORY IN ANALYZING CYBERWAR BETWEEN THE UNITED STATES AND CHINA - Fatima, Kharisma Putri Nur; Triwahyuni, Dewi (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2024)
This research aims to analyze cyberwar between the United States and China based on a constructivist perspective. Constructivism is an alternative view that offers the basic idea that international structure is a social construction. By using a qualitative approach, the results of this research show that according to a constructivist perspective, cyberwar is seen as anarchy, which means that war in cyberspace will remain a fantasy if the United States views China cooperatively. On the contrary, cyberwar will become a reality and have the impact of becoming a real war if the United States views China in a conflictual manner. The conclusion is, to ensure peace in cyberspace, the two countries need to interact with each other, so that there will be similarities in perception which can foster an attitude of mutual understanding, shared norms, and respect for identity which ultimately changes their perception as friends rather than enemies.